2010
DOI: 10.1159/000321596
|View full text |Cite
|
Sign up to set email alerts
|

Collision Tumor of Meningioma and Malignant Astrocytoma

Abstract: The authors report a 12-year-old boy who was presented with headache, nausea, vomiting and seizure. His magnetic resonance imaging showed 2 adjacent tumors in the region of the left ventricular trigone. The pathology of tumors reported collision tumors composed of meningioma and malignant astrocytoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Two articles were written in Persian [8, 12], whereas the remaining 33 were written in English. Most studies (n = 27) took place in Tehran province [4–5, 8, 1113, 15–23, 25–29, 3137] in hospitals and centers affiliated with the three main medical universities in Tehran: Tehran University of Medical Sciences (n = 16) [4–5, 11, 13, 1617, 1922, 26, 2829, 3132, 37], Shahid Beheshti University of Medical Sciences (n = 6) [12, 15, 18, 25, 27, 34,], Iran University of Medical Sciences (n = 4) [8, 23, 35, 36], and Army University of Medical Science (n = 1) [33]. Only four articles [18, 23, 26, 34] stated that approval by an ethics committee had been obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Two articles were written in Persian [8, 12], whereas the remaining 33 were written in English. Most studies (n = 27) took place in Tehran province [4–5, 8, 1113, 15–23, 25–29, 3137] in hospitals and centers affiliated with the three main medical universities in Tehran: Tehran University of Medical Sciences (n = 16) [4–5, 11, 13, 1617, 1922, 26, 2829, 3132, 37], Shahid Beheshti University of Medical Sciences (n = 6) [12, 15, 18, 25, 27, 34,], Iran University of Medical Sciences (n = 4) [8, 23, 35, 36], and Army University of Medical Science (n = 1) [33]. Only four articles [18, 23, 26, 34] stated that approval by an ethics committee had been obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, molecular features suggest a monoclonal tumor origin [18,19]. The second hypothesis is that the oligodendroglioma and sarcomatous tumor might have coexisted from before the first operation [20][21][22]. However, by following the intensive reexamination of the first radiological images and specimens, we could find no evidence that the sarcomatous components coexisted.…”
Section: Discussionmentioning
confidence: 79%
“…YJ Lu et al (2007) suggested that avoiding the complications associated with the transcranial approaches, extended transsphenoidal surgery might be a good alternative choice for approaching suprasellar meningioma and pituitary adenoma simultaneously (20). The ideal approach for treatment of such concomitant tumors is not clear due to lack of adequate experience in the literature (5,11,13,(22)(23)(24)(27)(28)(29)(30)(31)(32). Visual impairment was the main remaining complaint of both our patients after attempting to treat the PA either medically or surgically.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent adjacent double tumors in other locations of central nervous system (CNS) are even more implying the effect of unknown oncogenic factors (7). In this communication, we do not intend to report collision 'intrasellar' pathologies (12)(13)(14) but two cases of concomitant brain tumors (CCBT) are reported. Both tumors occurred in the sellar region.…”
Section: Background and Importancementioning
confidence: 97%